Perception of Employability in Regional Apparatus Organizations in Pesisir Selatan Regency, West Sumatra - Akmal, Akmal; Azliyanti, Elfitra (International Journal of Entrepreneurship and Business Management, 2023)
This study focused more on individuals as people who are employed about their work abilities. Individuals need to take responsibility for their personal development, recognize employability and view their careers in terms of broader employability across organizations within a contemporary career framework.  Research on the Perception of Employability needs to be done because some previous studies consider that employability is an organizational asset to improve performance and increase organizational flexibility. In this study, we tested 5 hypothesis that influence Perception of Employability, there are  leader-member exchange, the broad role of self-efficacy, organization-based self-esteem.  The data analysis applied Regression Analysis with SEM PLS. The response rate was 97.52% or as many as 323 questionnaires. The findings Leader-Member Exchange has a positive effect on the Perception of Employability, Leader-Member Exchange has a positive effect on Organization-Based Self-Esteem, Leader-Member Exchange has a positive effect on the extent of the role of self-efficacy. Organization-Based Self-Esteem has a positive effect on Perception of Employability and the extent of the role of self-efficacy has a positive effect on the Perception of Employability.